ANALISIS PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN DAN KONDISI EKONOMI MAKRO TERHADAP TINGKAT UNDERPRICING SAAT PENAWARAN UMUM PERDANA (Studi Empiris pada Perusahaan Go Publik yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2011) - David Tri Rachmadhanto; Raharja Raharja (Diponegoro Journal of Accounting, 2014)
This study aims to examine the variables that influence the level of underpricing stock price when the company's initial public offering in Indonesia Stock Exchange 2008-2011 period. The dependent variable in this study is the level of underpricing measured by value of initial returns, while the independent variable is the total asset turnover, debt to equity ratio, return on equity, current ratio, inflation rate, BI rate , and the exchange rate.  The data used in this study is a secondary data that collected by using purposive sampling method. Sample of 37 companies from 73  populations companies doing IPOs from 2008-2011 in Indonesia Stock Exchange. This study used multiple regression for data analysis. The results of this study showed that the variable debt to equity ratio negatively influence the level of underpricing is proven. Other variables such as total asset turnover, return on equity, current ratio, inflation rate, BI rate, and the exchange rate influence the level of underpricing is not proven. In this research model, shows the variable total assets turnover, debt to equity ratio, return on equity, current ratio, inflation rate, the BI rate, and the exchange rate can only explain the variation in the level of underpricing of 45 %.